2009
DOI: 10.1002/jcb.22283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro labeling of human umbilical cord mesenchymal stem cells with superparamagnetic iron oxide nanoparticles

Abstract: Human umbilical cord mesenchymal stem cells (hUC-MSCs) transplantation has been shown to promote regeneration and neuroprotection in central nervous system (CNS) injuries and neurodegenerative diseases. To develop this approach into a clinical setting it is important to be able to follow the fates of transplanted cells by noninvasive imaging. Neural precursor cells and hematopoietic stem cells can be efficiently labeled by superparamagnetic iron oxide (SPIO) nanoparticle. The purpose of our study was to prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…16 We have demonstrated in vitro that viability, cytokine production, and migratory capacity are unaffected by SPIO labeling. This is consistent with the majority of studies that have shown preservation of both viability and function after SPIO labeling of a variety of cell types including mesenchymal, hematopoietic, neural, and adipose-derived stem cells, [6][7][8][9][10][11] with only a few reporting adverse effects and 1 showing increased proliferation of SPIO-labeled mesenchymal stem cells. [17][18][19] It is worth recognizing the diversity in cell-labeling protocols used across these studies that may explain such findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…16 We have demonstrated in vitro that viability, cytokine production, and migratory capacity are unaffected by SPIO labeling. This is consistent with the majority of studies that have shown preservation of both viability and function after SPIO labeling of a variety of cell types including mesenchymal, hematopoietic, neural, and adipose-derived stem cells, [6][7][8][9][10][11] with only a few reporting adverse effects and 1 showing increased proliferation of SPIO-labeled mesenchymal stem cells. [17][18][19] It is worth recognizing the diversity in cell-labeling protocols used across these studies that may explain such findings.…”
Section: Discussionsupporting
confidence: 89%
“…SPIO are not toxic to cells and are biodegradable in vivo. [6][7][8][9][10][11] It is important to note, however, that the safety of intravenous administration of SPIO-labeled cells in humans has yet to be demonstrated, and would be critical for the development and Food and Drug Administration approval of novel clinical cell-tracking agents.…”
mentioning
confidence: 99%
“…The exponential fit of the experimental data in Figure 5B using relationship [2] was N SPION MAX = (6.58±0.74) × 10 4 and ξ =(22±7) µg/mL. After the internalization study of MION-Rh, the MIONRh intracellular internalization study was performed due to incubation concentration, according to the number of cells maintaining a constant MION-Rh concentration (40 µg Fe per mL), as seen in Figures 4C, 4D, and 5C.…”
Section: Quantification Of Mion-rh In Labeled Cellsmentioning
confidence: 99%
“…MSCs isolated from Wharton's Jelly (hUCMs (were shown to have surface markers, immune properties (Fong et al 2011;Weiss et al 2006), and differentiation potential towards cells with mesoderm offspring (Penolazzi et al 2009;Schneider et al 2010), including adipose, bone, cartilage, skeletal muscle, endothelium, cardiomyocyte and neuronal cells (Ishige et al 2009;Leeb et al 2009;Penolazzi et al 2009;Wu et al 2007), allowing replacement of ectodermal and mesodermal tissues (Schneider et al 2010). Several reports have characterized the in vitro differentiation capabilities of hUCM cells (La Rocca et al 2009) into neuron like cells (Abdulrazzak et al 2010;Cao and Feng 2009;Hu et al 2009;Zhang et al 2009b). Early studies focused on the differentiation of MSCs into neurons and detection of astrocyte markers received only modest attention (Boucherie and Hermans 2009).…”
Section: Introductionmentioning
confidence: 99%